Forensic medical approach to non-traumatic (pathological) cerebral haemorrhage cases - Dincer, Mesut; Soğukpınar, Veysel Osman; Üzün, İbrahim (The Bulletin of Legal Medicine, 2025)
Objective:Pathological deaths are an important part of forensic autopsies. This study’s objective was to assess, from a forensic perspective, non-traumatic (pathological) cases of cerebral hemorrhage, which hold a significant place among these types of deaths.Methods: This study retrospectively evaluated 252 cases where autopsies conducted in the relevant institution’s morgue department between January 1, 2013, and December 31, 2017, identified non-traumatic cerebral hemorrhage as the cause of death.Results: 73.4% of the 252 cases were male. It was observed that 52% of the cases were in the 5th and 6th decade. 52% had new traumatic findings such as ecchymosis, abrasion, laceration, while 33% had no traumatic findings or artifacts. 42.1% had subarachnoid hemorrhage, 19% had parenchymal hemorrhage, 37.7% had subarachnoid and parenchymal hemorrhage, and 1.2% had subdural hemorrhage only. Of the 100 cases of cerebral hemorrhage caused by aneurysm, 83 were subarachnoid hemorrhage, 16 were subarachnoid and parenchymal hemorrhage, and 1 was parenchymal hemorrhage. The medial cerebral artery and its bifurcation had the highest rate of aneurysms (37%). Drugs or stimulants were found in 15 cases, and 7 cases had blood ethanol levels higher than 100 mg/dL.Conclusion: Although deaths from pathological cerebral hemorrhages are classified as “natural death,” some cases involved death-contributing factors such as alcohol use, drug intake, cardiac findings, and infections. Emphasizing investigation to eliminate forensic suspicions, obtaining clinical data, and performing autopsies are essential to conclude the primary cause as “pathological cerebral hemorrhage” and the origin as “natural death.”
Keywords: Forensic medicine; forensic autopsy; subarachnoidal haemorrhage; parenchymal haemorrhage; Aneurysm